Can the Scala Mobile Explain the Fall and Rise of Earnings Inequality in Italy? A Semiparametric Analysis, 1977–1993 - Manacorda, Marco (Journal of Labor Economics, 2004)
This article uses Survey of Households' Income and Wealth microdata to investigate the role the Scala Mobile played in the initial fall and subsequent rise in earnings inequality in Italy between 1977 and 1993. The Scala Mobile was a wage indexation mechanism granting the same absolute wage increase to all employees as prices rose, thereby potentially compressing wage differentials. Over time, the potential equalizing effect of this mechanism fell. This article argues that the rise in inequality from the mid‐1980s was a response to the compression of differentials operated over the previous years by the Scala Mobile.